Knowledge and Attitude as Correlates of Participation in Recreation Activities among Members of Staff of a Tertiary Institution in Ekiti State, Nigeria - Ogunsile, Seyi; Alebiosu, Eunice; Bolarinwa, Olurotimi (Program Pascasarjana Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine the relationship between knowledge, attitude, and participation in recreational activities among members of staff of Ekiti State University (EKSU). The descriptive survey research design was adopted. Two hundred and one (201) members of staff of EKSU, selected through convenience sampling technique, from 8 faculties in EKSU, participated in the study. Data was collected with the aid of a self-developed and validated questionnaire and relationships among variables were determined using Pearson Product Moment Correlation analysis while differences were determined using t-test. Significance was set at P<0.05. The findings of this study revealed that 82.6%, 83.1%, and 66.7% of the respondents had a good knowledge, a positive attitude, and a moderate level of participation in recreational activities. Female respondents performed better in knowledge and participation in recreational activities. Also, respondents within the age range of 35-44years had a better attitude and participation in recreational activities. Knowledge had a significant positive relationship with attitude (r-0.365, P<0.05), and attitude also had a positive relationship with participation in recreational activities. (r=0.147, P<0.05). There was no significant difference between academic and non-academic staff in the knowledge, attitude, and participation in recreational activities. The outcome of this study suggests that having a good knowledge and a positive attitude are associated with a higher level of participation in recreational activities.